Design of Mechanically Agitated Fermenter for a Daily Ten Tons Ethanol Production from Cool- Feed Biomass - Fredrick Ugi; Benedict Ugi; Gloria Tamunotonye (ENP Engineering Science Journal)
This research designed a mechanically agitated fermenter that operates with the principles of heat exchanger, sustaining fermentation process in a conducive thermodynamic state which promotes product (ethanol) yield as well as its concentration (purity), with a target of achieving 10 tons per day ethanol from cool-feed biomass (palm wine). The design shows that the target was achieved at the fermenter vessel Area (A0) of 15.5917 m2 with the use of 1271.1646 kg/day coolant (water), operating at a conservative heat flow of 505262.484 J/day. MATLAB simulation was used to access the dynamic behavior of the agitated fermenter over a range of biomass and time. From the developed models, the result showed that the reaction rate of fermentation ((dC_L)/dt) was proportional to the overall mass transfer coefficient per unit volume of the biomass (K_L a) measured in per hours of the fermentation (hr-1). This can be due to decrease in the feed mass of a fermenter due to biomass decay which increases the oxygen penetrability of the system. Decrease in the fermenter material (biomass) due to biomass decay was also observed. This implies promotion of the fermentation rate of the system as the rate of biomass fermentation ((dC_L)/dt) decreases with increase in feed value of biomass. The residence time of the system was also reduced which implies that there was an increase in the fermentation rate of the biomass hence, promoting satisfactory product yield and purity which is one of the target of this research.